Analysis of the effectiveness of group tasks in e-learning of future teachers - Slikishina, Irina V.; Mozharov, Maksim S.; Mozharova, Anna E. (Opción, 2019)
This paper describes an experimental training course for future teachers using e-learning and students' independent work in small groups via an educational technology based on the following approaches: e-learning, small group learning, and project-based learning. As a result, the proposed educational technique increases students' involvement in independent learning activities and improves their quality, stimulating better prepared students to mentor the less prepared ones. In conclusion, the experiment described in this paper was aimed to confirm the assumption that the use of e-learning methods, combined with organizing students' independent work in small groups, could increase the effectiveness of training future teachers.